To Market, To Market - Miranda, Anne; Stevens, Janet (San Diego : Harcourt Brace, 1997)
Starting with the nursery rhyme about buying a fat pig at market, this tale goes on to describe a series of unruly animals that run amok, evading capture and preventing the narrator from cooking lunch.
Keywords: Nursery rhymes; Children's poetry